1993
DOI: 10.1192/pb.17.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Consumer audit of psychiatric training

Abstract: Postgraduate psychiatric training is usually assessed by regular College visits. A number of training schemes, including the Liverpool training scheme, also scrutinise their training independently of the College. As far as we know, trainees as the ‘consumers’ of training have never assessed its quality themselves. The following account deals with two such audits in the Mersey region organised under the mantle of the Association of Liverpool Psychiatrists in Training (ALPIT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A trainees’ charter, which would define the trainee’s rights to supervision, feedback, support, decent working conditions and respect, was suggested [55]. Cunningham and Carmelo challenged the utility of the RCP’s audit panels, on the grounds that trainees feared being ‘singled out as troublemakers’ if they expressed frank opinions about supervision [56]. They conducted their own audit, which found that supervision was generally thought to be unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A trainees’ charter, which would define the trainee’s rights to supervision, feedback, support, decent working conditions and respect, was suggested [55]. Cunningham and Carmelo challenged the utility of the RCP’s audit panels, on the grounds that trainees feared being ‘singled out as troublemakers’ if they expressed frank opinions about supervision [56]. They conducted their own audit, which found that supervision was generally thought to be unsatisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…While clearly they have one view of supervision, it is important to recognize that their view will be different from that of trainees. Some of the writing by trainees outlined the reasons why they may feel intimidated and reluctant to complain openly about their training and showed the different result obtained when an audit was conducted by trainees, rather than by the RCP [56]. This would imply that if the College wishes to know the realities of supervision from the trainees' perspective it must find safe, anonymous means for them to give information without fear of the consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of training should indeed be a mandatory requirement of employing authorities. A consumer audit of the training (Cunningham & Aquilina, 1993) would be helpful in order to have a better understanding of needs and improve performance of future training. It is hoped that the training needs and opinions of psychiatrists in non-training posts will be taken more into account in the future.…”
Section: Recommendations and Conclusionmentioning
confidence: 99%
“…Trainees sent in articles on their audit of psychiatric training (Cunningham & Aquilina, 1993), psychiatry in Kuwait, details of local mental health self-help groups, a review of key papers in forensic psychiatry, reports from ALPIT representa tives in the regional committees, forthcoming local courses and talks. A gossip column and a few cartoons provided the necessary comic relief.…”
Section: Revivingmentioning
confidence: 99%